KERUKUNAN ANTAR SUKU DALAM MASYARAKAT MULTIKULTURAL DI TRANS SP 4 KECAMATAN JANGKANG KABUPATEN SANGGAU - Dedeh Winarsih; Aminuyati Aminuyati; Hadi Wiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to determine the role of society in creating harmony, and todetermine the factors that influence the harmony that exists in a multiculturalsociety in Trans SP 4, Jangkang District, Sanggau Regency. The form of researchused in this study is descriptive qualitative with data sourced from the community(primary data) and photo documentation (secondary data). Data collectiontechniques used are observation, interviews and documentation. The study's resultsshow that (1) the community's role in cultivating harmony takes the shape ofcooperation, mutual respect, and mutual trust, as evidenced by the community suchas cleaning cemeteries, helping neighbors in building houses, cleaning roads, andcooperating in farming. (2) Factors that influence community peace includeinteractions between ethnic groups, such as social greetings, tolerance, which ispromoted by learning the arts, languages, and cultural customs of other ethnicgroups, and assisting one another in the construction of religious buildings.Furthermore, regardless of ethnicity or religion, there is a common need to meeteconomic and social goals through blending together.Keywords: Interethnic Harmony, Multicultural, Society.